Effects of CYP2C19*17 Genetic Polymorphisms on the Steady-State Concentration of Diazepam in Patients With Alcohol Withdrawal Syndrome. (October 2021) - Skryabin, Valentin Yurievich; Zastrozhin, Mikhail; Torrado, Marco; Grishina, Elena; Ryzhikova, Kristina; Shipitsyn, Valery; Galaktionova, Tatiana; Sorokin, Alexander; Bryun, Evgeny; Sychev, Dmitry
Background: Diazepam is one of the most widely prescribed tranquilizers for the therapy of alcohol withdrawal syndrome (AWS), which includes the symptoms of anxiety, fear, and emotional tension. However, diazepam therapy often turns out to be ineffective, and some patients experience dose-dependent adverse drug reactions, reducing the efficacy of therapy.Aim: The purpose of our study was to investigate the effects of CYP2C19*17 genetic polymorphisms on the steady-state concentration of diazepam in patients with AWS.Materials and Methods: The study was conducted on 50 Russian male patients suffering from the AWS. For the therapy of psychomotor agitation, anxiety, fear, and emotional tension, patients received diazepam in injections at a dosage of 30.0 mg/day for 5 days. Genotyping was performed by real-time polymerase chain reaction. The efficacy and safety assessment was performed using psychometric scales and scales for assessing the severity of adverse drug reactions. Therapeutic drug monitoring (TDM) was performed using the high-performance liquid chromatography-mass spectrometry (HPLC-MS/MS) method.Results: Based on the results of the study, we revealed the differences in the efficacy of therapy in patients with different CYP2C19 − 806C>T genotypes: (*1/*1) −12.0 [−15.0; −8.0], (*1/*17+*17/*17) −7.0 [−14.0; −5.0], P  < .001, as well as the results of TDM: ( CC ) 250.70 [213.34; 308.53] ng/mL (*1/*17+*17/*17) 89.12 [53.26; 178.07] ng/mL, P  < .001.Conclusion: Thus, our study enrolling 50 patients with AWS, showed the effects of CYP2C19*17 genetic polymorphisms on the efficacy and safety rates of diazepam. Furthermore, we revealed the statistically significant difference in the levels of plasma steady-state concentrations of diazepam in patients carrying different genotypes.